2016
DOI: 10.1177/1558944716661992
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Therapeutic Whirlpool and Hot Packs on Hand Volume During Rehabilitation After Distal Radius Fracture: A Blinded Randomized Controlled Trial

Abstract: Whirlpool is a potential consideration when selecting a heat modality for patients with DRF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…As a strategy in nonpharmacological interventions, heat therapy is used as an effective approach to improving cardiovascular function, relaxation of muscles, improving local blood flow, and increasing joint range of motion [ 29 , 30 ]. Other nonpharmacological interventions, such as aromatherapy, acupuncture, cognitive-behavioral therapy (CBT), yoga, physical exercise, sleep hygiene training, vibration, and massage techniques, have been used to relieve the symptoms of RLS [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a strategy in nonpharmacological interventions, heat therapy is used as an effective approach to improving cardiovascular function, relaxation of muscles, improving local blood flow, and increasing joint range of motion [ 29 , 30 ]. Other nonpharmacological interventions, such as aromatherapy, acupuncture, cognitive-behavioral therapy (CBT), yoga, physical exercise, sleep hygiene training, vibration, and massage techniques, have been used to relieve the symptoms of RLS [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Disagreements were settled through discussion and agreement. Figure 1 (2017) [13] The Effect of Therapeutic A study on the epidemiology of DRF predicted risk factors and prognosis and found the responsive factors of chronic disability and pain, which lead to an imperative perspective for therapists to implement more extensive assessment, interventional strategies, and customized educational programs. This leads to the conclusion that DRF is the most common fracture worldwide with a need for rehabilitation to return to functional ADLs [11].…”
Section: Methodsmentioning
confidence: 99%
“…In a blinded randomized controlled trial (RCT), whirlpool was considered a reliable method of applying heat over the affected site post-DRF. This mentioned that conventionally, hot packs and whirlpool effectively improve the volume of the hands in DRF patients following functional recovery [ 13 ].…”
Section: Reviewmentioning
confidence: 99%
“…3 In terms of disease burden, 63% of people with upper limb fracture report ongoing pain 6 months post fracture, and up to 15% develop complications such as persistent neuropathies, long-term impairment, and complex regional pain syndrome. [4][5][6] In adults aged over 50 years old, wrist fractures are likely to represent a fragility fracture, defined as fractures which occur following an episode of low trauma. 7,8 Such fractures are often the first indicator of poor bone health and are associated with debilitating consequences with respect to activities of daily living such as work, driving, mobility, and self-care, leading to: loss of independence; re-fracture at other sites; reduced quality of life; increased health and social care consumption; and up to a 14% increase in mortality rates 7 years post-fracture.…”
Section: R I P T [H1]backgroundmentioning
confidence: 99%